An autonomous quantum machine to measure the thermodynamic arrow of time. (December 2018) - Monsel, Juliette; Elouard, Cyril; Auffèves, Alexia
Abstract According to the second law of thermodynamics, the evolution of physical systems has a preferred direction, that is characterized by some positive entropy production. Here we propose a direct way to measure the stochastic entropy produced while driving a quantum open system out of thermal equilibrium. The driving work is provided by a quantum battery, the system and the battery forming an autonomous machine. We show that the battery's energy fluctuations equal work fluctuations and check Jarzynski's equality. As these energy fluctuations are measurable, the battery behaves as an embedded quantum work meter and the machine verifies a generalized fluctuation theorem involving the information encoded in the battery. Our proposal can be implemented with state-of-the-art opto-mechanical systems. It paves the way toward the experimental demonstration of fluctuation theorems in quantum open systems. Quantum thermodynamics: measuring entropy production at the quantum level An opto-mechanical device coupled to a qubit could be able to directly measure entropy generation in an open quantum system. Alexia Auffèves and Juliette Monsel from Université Grenoble Alpes and Cyril Elouard from University of Rochester show that a system composed by a nanomechanical device (such as a tiny membrane) strongly interacting with a two-level system (for example a quantum dot) could potentially provide a feasible way to test entropy production when put into contact with en external bath. Entropy generation is also called "thermodynamic arrow of time" because it's what drives the evolution of physical system along a preferred direction. Up to now its verification at the quantum level has been limited to isolated systems, but the authors' proposal could help experimentalists to fill this gap.